If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -43 + 7x = 29 + x Solving -43 + 7x = 29 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -43 + 7x + -1x = 29 + x + -1x Combine like terms: 7x + -1x = 6x -43 + 6x = 29 + x + -1x Combine like terms: x + -1x = 0 -43 + 6x = 29 + 0 -43 + 6x = 29 Add '43' to each side of the equation. -43 + 43 + 6x = 29 + 43 Combine like terms: -43 + 43 = 0 0 + 6x = 29 + 43 6x = 29 + 43 Combine like terms: 29 + 43 = 72 6x = 72 Divide each side by '6'. x = 12 Simplifying x = 12
| 6-(-54/7) | | 17+b=25 | | 6/7*-9 | | 16+3x= | | -46+5x=-x+56 | | y=16+3x | | 2-30/39 | | 6-(-57/7) | | 68/13-4 | | -59+2x=16-3x | | -5x+1oy=0 | | 10x+18=5x+138 | | 2x^2-12=116 | | 204/39 | | -113+5x=-9x+41 | | 6x-3=16-63 | | 3x-9=-13 | | 8Y-5=4A-3 | | 7(1)+3(2)= | | 9x-40=60+4x | | 12x^2+17x-13=-8 | | 12+32=12x-7 | | 4x+12=30-6x | | 3x+8y-5x-1y=0 | | 7d-2=14d-9 | | 15c^2+60=45 | | 5a+6b=50 | | 8-(-9/4) | | -25-2x=-108-8x | | 8-9/4 | | 6b+12=b+42 | | -[9z-(12z+8)]=8+(2z+10) |